Reduced Notch signalling leads to postnatal skeletal muscle hypertrophy in Pofut1(cax/cax) mice - Al Jaam, Bilal (Open Biol, 2016)
Postnatal skeletal muscle growth results from the activation of satellite cells and/or an increase in protein synthesis. The Notch signalling pathway maintains satellite cells in a quiescent state, and once activated, sustains their proliferation and commitment towards differentiation. In mammals, POFUT1-mediated O-fucosylation regulates the interactions between NOTCH receptors and ligands of the DELTA/JAGGED family, thus initiating the activation of canonical Notch signalling. Here, we analysed the consequences of downregulated expression of the Pofut1 gene on postnatal muscle growth in mutant Pofut1(cax/cax) (cax, compact axial skeleton) mice and differentiation of their satellite cell-derived myoblasts (SCDMs). Pofut1(cax/cax) mice exhibited muscle hypertrophy, no hyperplasia and a decrease in satellite cell numbers compared with wild-type C3H mice. In agreement with these observations, Pofut1(cax/cax) SCDMs differentiated earlier concomitant with reduced Pax7 expression and decrease in PAX7(+)/MYOD(−) progenitor cells. In vitro binding assays showed a reduced interaction of DELTA-LIKE 1 ligand (DLL1) with NOTCH receptors expressed at the cell surface of SCDMs, leading to a decreased Notch signalling as seen by the quantification of cleaved NICD and Notch target genes. These results demonstrated that POFUT1-mediated O-fucosylation of NOTCH receptors regulates myogenic cell differentiation and affects postnatal muscle growth in mice.